2020
DOI: 10.1002/solr.202000582
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Perovskite Solar Cells by Fluorinated Ionic Liquid–Induced Component Interaction

Abstract: Because of the high absorption coefficient, [1] extra-long carrier diffusion lengths, [2] excellent optoelectronic properties, [3] single junction organic halide perovskite solar cells (PSCs) have attracted great attention, [4] as their certified power conversion efficiencies (PCEs) have experienced unprecedentedly rapid increase from 3.8% to 25.5% over the past decade. [5] Given the outstanding photovoltaic performance, PSCs have been treated as a promising candidate for next-generation high-performance solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…This anchoring effect of the IL BMIBr suppresses the ion migration and loss of MA + from the perovskite film, leading to improved thermal stability of the film. Moreover, our group also demonstrated that the fluorinated IL methyl­ammonium difluoro­acetate (MA + DFA – ) can interact with MAPbI 3 perovskite to effectively improve its stability . Recently, Bai et al reported that introducing a small amount of the IL 1-butyl-3-methyl­imidazolium tetrafluoro­borate (BMIMBF 4 ) in MAPbI 3 perovskite (Figure d) could significantly improve the photovoltaic performance and long-term stability of PSCs.…”
Section: Functions and Mechanisms Of Ils In Pscsmentioning
confidence: 79%
See 1 more Smart Citation
“…This anchoring effect of the IL BMIBr suppresses the ion migration and loss of MA + from the perovskite film, leading to improved thermal stability of the film. Moreover, our group also demonstrated that the fluorinated IL methyl­ammonium difluoro­acetate (MA + DFA – ) can interact with MAPbI 3 perovskite to effectively improve its stability . Recently, Bai et al reported that introducing a small amount of the IL 1-butyl-3-methyl­imidazolium tetrafluoro­borate (BMIMBF 4 ) in MAPbI 3 perovskite (Figure d) could significantly improve the photovoltaic performance and long-term stability of PSCs.…”
Section: Functions and Mechanisms Of Ils In Pscsmentioning
confidence: 79%
“…Moreover, our group also demonstrated that the fluorinated IL methylammonium difluoroacetate (MA + DFA − ) can interact with MAPbI 3 perovskite to effectively improve its stability. 92 Recently, Bai et al 74 reported that introducing a small amount of the IL 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF 4 ) in MAPbI 3 perovskite (Figure 9d) could significantly improve the photovoltaic performance and long-term stability of PSCs. Through the XPS spectra of the perovskite film surface (Figure 9e) and time-of-flight secondary-ion mass spectrometry (ToF-SIMS) of the perovskite bulk (Figure 9f,g), it can be demonstrated that the anions and cations of BMIMBF 4 are not identically distributed in the perovskite film.…”
Section: ■ Functions and Mechanisms Of Ils In Pscsmentioning
confidence: 99%
“…To improve the optoelectronic performance of PSCs, many efforts have been devoted such as exploiting novel charge transport materials, , composition engineering of perovskites, , interfacial modification, and so on. SnO 2 has been considered as a promising ETL for PSCs because SnO 2 has a deeper conduction band than TiO 2 , faster electron mobility, and more favorable energy level alignment. , In our previous studies, morphologically regulated SnO 2 nanocrystals were synthesized for PSCs, which display improved electron transport because of their specially designed architectures. However, defects and trap sites including Sn interstitials and O vacancies usually exist in SnO 2 nanocrystals, which are detrimental to electron transport and give rise to charge recombination .…”
Section: Introductionmentioning
confidence: 99%
“…To further suppress the ion migration within the HTL-free PSCs and trilayer PSC, PFTeDA with 27 fluorine atoms and a carbonyl unit was introduced as an additive in the system (referred to as target in the following text). Organic molecules with carbonyl units have been introduced into the MAPbI 3 system for efficient ion migration suppression and defect passivation since they will locate at surface and grain boundaries due to the chelation between the noncoordinating lead and carbonyl unit. , The carbon fluorine bonds exhibit highly hydrophobic chemical properties which induce kinetic barriers that slow the ion migration of MA + /I – and intrusion of O 2 and H 2 O. ,, Thus, in this study, the incorporation of PFTeDA is designed for efficiently blocking the ion migration, passivating crystal defects, and enhancing overall device stability in the MAPbI 3 -based CTL-free PSCs. The cross-section SEM image of a HTL-free PSC can be found in Figure a, the perovskite film was compactly coated on the FTO/SnO 2 substrate, and the carbon electrode was densely deposited on top of the perovskite light absorber.…”
mentioning
confidence: 99%
“…Organic molecules with carbonyl units have been introduced into the MAPbI 3 system for efficient ion migration suppression and defect passivation since they will locate at surface and grain boundaries due to the chelation between the noncoordinating lead and carbonyl unit. 46,47 The carbon fluorine bonds exhibit highly hydrophobic chemical properties which induce kinetic barriers that slow the ion migration of MA + /I − and intrusion of O 2 and H 2 O. 46,48,49 Thus, in this study, the incorporation of PFTeDA is designed for efficiently blocking the ion migration, passivating crystal defects, and enhancing overall device stability in the MAPbI 3 -based CTL-free PSCs.…”
mentioning
confidence: 99%